Excessive body weight and its relationship to body image in teenagers aged 16–18 years old in South Jakarta - Dania Mirza Ramadhanty; Bernie Endyarni Medise (World Nutrition Journal, 2020)
Objective. Overweight is one of the health problems that often occur in children and adolescents throughout the world, both in developed and developing countries. Study results in USA showed yearly increase of overweight prevalence in children aged 2–19 years old. In addition, based on the results by the National Health and Nutrition Examination Survey 2009–2010 in United States, the highest percentage of overweight and obesity by age group was found at 12–19 years old (33.6%). Basic Health Research/Riskesdas’s data in 2013 showed the prevalence of overweight in adolescents aged 16–18 years old in Indonesia reached the highest value of 11.5%. Moreover, most teenagers see their body images as a match between self’s and others’ ideal perception. Teenagers with positive body image tend to be more confident and also easier to get along with other people, especially their peers. In this study, researcher aimed to investigate the relationship between teenagers who have excess body weight with body image, whether it had positive or negative impact.Methods: This was a cross-sectional study. Data collection was done from December 2017 to January 2018. Data collected were anthropometric measurements (weight and height) and the King College London Body Image Questionnaire's filled by participants. From 400 subjects who filled the questionnaires, a total of 350 participants matched the inclusion criteria and were analyzed. Chi square test was done as data analysis.Results: Chi-square analysis for excess body weight status in relation to body image scores showed no relationship (p=1,000).Conclusions: There was no significant relationship between excessive body weight and body image.